Ethical competence-exploring situations in physiotherapy practice - Naamanka Kati; Suhonen Riitta; Tolvanen Anna; Leino-Kilpi Helena (TAYLOR & FRANCIS INC, 2025)
Introduction
Ethical competence is a key area of professional expertise in physiotherapy. It is needed for successful interaction and rehabilitation - most physiotherapists encounter ethical situations weekly, but the ability to recognize and meet these situations varies.
Objective
This study describes physiotherapists' ethical competence in situations in which they experience they have succeeded to act ethically competently. The study also seeks to verify an existing conceptual frame, developed through a concept analysis of ethical competence.
Method
All together 164 physiotherapists responded to open-ended questions by writing short narratives of an ethically challenging situation. The narratives which were analyzed using deductive-inductive content analysis to discover meaningful underlying categories under the existing analysis frame's themes.
Results
Responses were related to advocating and supporting patients, identifying barriers in own knowledge and implementing physiotherapy according to the patient's needs, even if the treatment wasn't in line with the actual goals or organization's guidelines. Ethical awareness as an attribute of ethical competence was emphasized in physiotherapists' responses.
Conclusion
This study provided new knowledge about ethically challenging situations that physiotherapists encounter and their abilities to work within these. As all the attributes of ethical competence were present in the situations described, it can be stated that the analysis frame at this point is adequate. Further testing of the frame should be done to gain data-driven trustworthiness and credibility.